2016
DOI: 10.3389/fpls.2016.00121
|View full text |Cite
|
Sign up to set email alerts
|

5-Aminolevulinic Acid Thins Pear Fruits by Inhibiting Pollen Tube Growth via Ca2+-ATPase-Mediated Ca2+ Efflux

Abstract: Chemical fruit thinning has become a popular practice in modern fruit orchards for achieving high quality fruits, reducing costs of hand thinning and promoting return bloom. However, most of the suggested chemical thinners are often concerned for their detrimental effects and environmental problems. 5-Aminolevulic acid (ALA) is a natural, nontoxic, biodegradable, and environment-friendly plant growth regulator. One of its outstanding roles is improving plant photosynthesis and fruit quality. Here, results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 30 publications
(48 reference statements)
0
18
0
Order By: Relevance
“…In plants, ALA, a natural plant growth regulator, has attracted increasing attention due to its various physiological roles and great application potential in agriculture and horticulture (Wang et al , Akram and Ashraf , Feng et al , An et al , , Zheng et al , An et al , Zheng et al ). We previously demonstrated a new role of ALA in regulating stomatal movement and revealed that H 2 O 2 signaling is crucial in ALA‐regulated stomatal movement (An et al ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In plants, ALA, a natural plant growth regulator, has attracted increasing attention due to its various physiological roles and great application potential in agriculture and horticulture (Wang et al , Akram and Ashraf , Feng et al , An et al , , Zheng et al , An et al , Zheng et al ). We previously demonstrated a new role of ALA in regulating stomatal movement and revealed that H 2 O 2 signaling is crucial in ALA‐regulated stomatal movement (An et al ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been recognized as a vital plant growth regulator due to its various roles in several key physiological processes such as promoting plant growth and conferring abiotic stress tolerance in plants , Niu et al 2017, Sun et al 2017, Akram et al 2018, Liu et al 2018, Wu et al 2018. Increasing attention has been paid to ALA because of its environmental-friendly Abbreviations -ABA, abscisic acid; ALA, 5-aminolevulinic acid; AsA, ascorbic acid; BR, brassinosteroid; CalA, calyculin A; CAT, catalase; DPI, diphenylene iodonium; GFP-TUA6, green fluorescent protein-tagged -tubulin 6 transgenic Arabidopsis; H 2 O 2 , hydrogen peroxide; MeJA, methyl jasmonate; MS, Murashige and Skoog; MTs, microtubules; OA, okadaic acid; OE, overexpression; PP2A, type 2A protein phosphatase; PP2A-C2, C2 subunit of type 2A protein phosphatase; PP2A-C2-OE, PP2A-C2 overexpression; PPFD, photosynthetic photo flux density; ROS, reactive oxygen species; VBT, vinblastine. characteristic and great application potential in agriculture (Wang et al 2003, Akram andAshraf 2013) and horticulture (Feng et al 2016, An et al 2016b, Zheng et al 2017, Zheng et al 2018. Our recent studies suggested a new role of ALA, regulating stomatal movement (An et al 2016a(An et al , 2016c.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Another P 2B ‐type isoform, ACA7, is expressed exclusively in developing pollen grains and is required for normal pollen development (Lucca & Leon, ). Indeed, significant negative correlations between Ca 2+ ‐ATPase activity and pollen germination exist (An et al ., ). AtACA10 regulates a vegetative phase development and inflorescence architecture in Arabidopsis (Huda et al ., ,b), while ACA8 plays a role in sucrose signalling during early seedling development (Zhang et al ., ).…”
Section: Ca2+ Extrusion Systemsmentioning
confidence: 97%
“…5-Aminolevulinic acid (ALA), a key biosynthetic precursor for tetrapyrrole compounds in all living animals, plants, and microorganisms, has been proved as an environmentfriendly new plant growth regulator (Wu et al 2019). It regulates many physiological processes of plants, including seed germination (Wang et al 2005), guard cell movement and photosynthesis (An et al 2016a, c), pollen germination and tube growth (An et al 2016b), fruit coloration (Feng et al 2016), and resistance to almost all kinds of abiotic stresses (Akram and Ashraf 2013). Increasing evidence suggests a great application potential of ALA in agriculture (Wang et al 2003).…”
Section: Introductionmentioning
confidence: 99%